FROM SCENES TO SPACES - HENRIKSSON, JENNIFER; ULVESTIG, AMANDA (My University, 2023)
he home could be described as a theatre stage in which everyday life takes place in different scenes. Each of these scenes have disparate demands on the space, which needs to be adaptable to facilitate the needs in the individual scenarios, especially when living in a small space. The number of solo households in Europe are increasing, about one third of all households are solo households. In the Nordic countries this number is even higher. At the same time, the dwelling sizes have decreased. This puts new demands on the living spaces as solo dwellers often experience a shortage of space in their small apartments. Student housing is often small, and excepted from standards commonly applied to regular apartments. This type of dwelling could therefore benefit from new, innovative, living solutions. Many students who move to a new city to study, will only live there for a limited period of time. This, in combination with often limited finances and social connections in the new city, can make it difficult to buy and transport furnishings for an empty apartment. This thesis explores the spatial configuration within a 33 sqm apartment where movable modules facilitate all basic needs of the home. The modules concurrently enable the dweller(s) to decide if they want to distribute their living space into one, two or three rooms. The partitioning can be set for a longer period of time as well as being changed daily depending on the dwellers’ routine. Through spatial and design explorations as well as theoretical studies this thesis aims to create an understanding of how our homes are used and what scenes they need to support. The thesis result consists of a design proposal for student housing with a flexible construction and apartment layout, without the need of added furniture. The design proposal is implemented on Gibraltarvallen in Gothenburg.
Keywords: architecture, flexibility, configurability, scenes, activities, apartments, student housing